Pencitraan Inframerah Dekat dari Lemak Sapi pada Model Lemak Tissue - Chrisli Elfri Sahuleka (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2019)
All women concern for their beauty. Some ways are done to obtain beauty with the use of creams, routine care in beauty clinics, up to plastic surgery by having liposuction on the desired part of the face. In the early procedures of plastic surgery, a 2-4cm incision is made on the skin before sucking the fat out. This cutting can cause various risks. Therefore, a non-destructive method is needed to identify the position of fat as a pre-plastic surgery procedure. Near Infrared Spectroscopy is a method for quickly and precisely identifying and measuring a sample without damaging it. This study aims to determine the area spectral and or wavelength sensitivity for fat and several other important components and to determine the position of fat from a one-dimensional image. The results show that the location of fat is in position 11-28. From this, it can be concluded that NIRS can inform the position of fat from a one-dimensional image.